Development of Negotiation Text Teaching Materials in the Form of E-Comic Assisted by Class X Comic Life Application - Lestari, Putri Ayu; Lubis, Fitriani (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the development process and the feasibility of teaching materials for negotiating texts in the form of e-comics assisted by the comic life application for class X. This research uses the R&D (Research and Development) method using 7 stages of development which have been simplified according to the needs and abilities of researchers during the process. research implementation. The results of the study show that 1) the process of developing teaching materials for negotiating texts is in the form of e-comics, which starts with an analysis of potentials and problems, data collection in the form of analysis of student needs, analysis of teacher's lesson plans, and analysis of teaching materials. The next stage is product design, material and design validation tests carried out by design expert validators and material expert validators, then the material and design revision stage, the product trial stage in the form of student responses, and the final stage in the form of the final product. The final product produced is in the form of teaching material for negotiating text in the form of an e-comic in the form of a PDF so that it can be accessed via mobile phones on the WhatsApp, Line, Telegram and similar applications with the help of an internet connection. 2) The feasibility of teaching material for negotiating text in the form of e-comics from the material validator obtained a result of 80% (Feasible), an assessment from the design validator obtained a result of 80% (Eligible), the assessment of Indonesian teachers obtained a result of 90% (Very feasible), and the assessment of class X MIPA 2 students obtained a result of 81.1% (Very feasible). Based on the results of this assessment, it can be concluded that the teaching materials for negotiating text developed in the form of e-comics are suitable for learning Indonesian in schools.